2012
DOI: 10.5507/bp.2012.051
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E polymorphism is associated with both number of diseased vessels and extent of coronary artery disease in Czech patients with CAD

Abstract: Aims. The impact of ApoE polymorphism on angiographic parameters was assessed in patients referred for coronary angiography. Methods. Elective coronary angiography was performed in 671 subjects (525 men, 146 women, mean age 60±10 years) with symptoms of ischemic heart disease. The patients were divided into: no CAD group (smooth coronary vessels, n=83), one-vessel (n=155), two-vessel (n=170) and three-vessel disease (n=196). Patients with stenoses 0-50% were excluded. Within patients with CAD, we evaluated ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
(64 reference statements)
1
2
0
1
Order By: Relevance
“…ApoE33 genotypes (72.5%) were the most common genotypes. This is a universal finding for human populations that was supported by many previous studies [9][10][11][12]. The frequency of the ApoE2 alleles (E22 + E23) and ApoE4 alleles (E34 + E44) is 9 and 18.5%, respectively.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…ApoE33 genotypes (72.5%) were the most common genotypes. This is a universal finding for human populations that was supported by many previous studies [9][10][11][12]. The frequency of the ApoE2 alleles (E22 + E23) and ApoE4 alleles (E34 + E44) is 9 and 18.5%, respectively.…”
Section: Discussionsupporting
confidence: 70%
“…They found that there were no statistically significant differences between ApoE genotypes and severity of CAD by using the Gensini score. However, the study team of Dr. Jan Machal [9] reported different results. They found that the frequency of the ApoE23 genotype was lower in the 3-vessel disease group compared to 1-vessel disease, 2-vessel disease or no CAD group.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Ačkoliv předchozí studie prokázaly souvislost nosičství alely 2 s nižším výskytem nemoci tří tepen a fokálním charakterem lézí [12], v našem souboru jsme neprokázali žádný vztah mezi genotypem APOE a rozsahem koronární aterosklerózy (nemoc více tepen, komplexní léze B2/C) nebo výskytem akutních koronárních syndromů. Taktéž jsme neprokázali signifi kantní rozdíly v systolické funkci traci APOE a taktéž up-regulaci jaterních receptorů LDL a snížení koncentrace LDL cholesterolu [5].…”
Section: Diskuseunclassified